Facebook-based Tourism Promotion in Indonesia - Amin Kiswantoro; Eufemia Sarina; Azril Azahari; Nur Rohman (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Promoting a tourist destination, Facebook is one of the best social media platfroms can be employed. Facebook has been known by everyone for a long time and hence even though there are many new features, people are still using Facebook. By posting on Facebook wall, most young people shared something including tourism promotion. They will post photos or videos with exciting words and greetings to other polite users. Indeed, previously tourism promotion was still minimal because many people were not familiar with social media. But along with the times, their mindset changed. They learn to use social media and at the same time make tourism is getting more intense in Indonesia. Here we will briefly discuss Facebook as a medium for promoting tourism in Indonesia. We present a review on the usage of Facebook as a platform for tourism promotion made by many scholars in Indonesia. We further present a discussion on what should tourism business player should do on their Facebook promotion page. Finally, we present open problems for future research recommendations.